Effects and Reversibility of Pre- and Post-natal Iron and Omega-3 Fatty Acid Deficiency, Alone and in Combination, on Bone Development in Rats - Strydom, Estelle; Zandberg, Lizelle; Kemp, Erna T.; Venter, Philip vZ.; Smuts, Cornelius M.; Kruger, Herculina S.; Baumgartner, Jeannine (Frontiers in Nutrition, 2022)
Both iron and omega-3 (n-3) polyunsaturated fatty acids may play an important role in bone development. The aim of this study was to investigate the effects of pre- and post-natal iron and n-3 fatty acid deficiency (FAD), alone and in combination, on bone development in rats, and to determine whether effects are reversible when a sufficient diet is provided post-weaning. Using a 2×2-factorial design, 56 female Wistar rats were allocated to one of four diets: (1) control, (2) iron deficient (ID), (3) n-3 FAD or (4) ID and n-3 FAD, and were maintained on the respective diets throughout gestation and lactation. At weaning (post-natal day [PND] 21), offspring (n = 24/group; male:female=1:1) were randomly allocated to either continue with their respective diets or to switch to the control diet until PND 42-45. Bone mineral density (BMD) and bone strength were determined using dual X-ray absorptiometry and three-point bending tests, respectively. Pre- and post-natal ID resulted in significantly lower BMD in the spine and bone strength in the left femur. Both ID and n-3 FAD resulted in lower BMD in the right femur, with an additive reduction in the combined ID and n-3 FAD group vs. controls. While negative effects of pre- and post-natal ID alone were reversed in offspring switched to a control diet post-weaning, lower BMD and bone strength persisted in offspring with combined ID and n-3 FAD during the prenatal and early post-natal period. Effects were not sex-specific. These results indicate that ID during early life may negatively influence bone development, with potential additive effects of n-3 FAD. While the effects of ID alone seem reversible, a combined ID and n-3 FAD may result in irreversible deficits in bone development.